2022
DOI: 10.2147/jhc.s382226
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatase 2 Along with Syndecan 1 and Glypican 3 Serum Levels are Associated with a Prognostic Value in Patients with Alcoholic Cirrhosis-Related Advanced Hepatocellular Carcinoma

Abstract: Sulfatase 2 (SULF2) is an enzyme related to heparan sulfate modifications. Its expression, as for some heparan sulfate proteoglycans expression, has been linked to hepatocellular carcinoma (HCC) at mRNA level and immunohistochemistry staining on biopsy samples. This study aims to evaluate the prognostic value of serum levels of SULF2 in patients with alcoholic cirrhosis with or without HCC. Patients and Methods: Two hundred and eighty-seven patients with alcoholic cirrhosis were enrolled in this study: 164 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Studies have shown that GPC3 expression levels in HCC tissues are associated with tumor aggressiveness and poor prognosis, including tumor size, vascular invasion, and metastasis ( 36 , 37 ). Elevated serum levels of GPC3 have also been associated with worse overall survival and disease-free survival in patients with HCC ( 38 ). Based on these data, GPC3 may be useful for stratifying HCC patients based on their prognosis and guiding treatment decisions.…”
Section: Hcc Biomarkers: From Disease Surveillance To Therapeutic Tar...mentioning
confidence: 99%
“…Studies have shown that GPC3 expression levels in HCC tissues are associated with tumor aggressiveness and poor prognosis, including tumor size, vascular invasion, and metastasis ( 36 , 37 ). Elevated serum levels of GPC3 have also been associated with worse overall survival and disease-free survival in patients with HCC ( 38 ). Based on these data, GPC3 may be useful for stratifying HCC patients based on their prognosis and guiding treatment decisions.…”
Section: Hcc Biomarkers: From Disease Surveillance To Therapeutic Tar...mentioning
confidence: 99%